Penerapan Prinsip-Prinsip Good Governance dalam Pelayanan BPJS Kesehatan di Kota Padang - Citra Rosika; Aldri Frinaldi (Publikasi Indonesia, 2023)
In order to realize democratic principles, which are a reflection of upholding aspects of citizens' rights by the government and upholding the values of justice and social solidarity as well as human rights in various aspects of state life, the application of good governance or a system of good governance is indispensable. One of the concrete manifestations of the implementation of good governance is the realization of the sustainability of BPJS Kesehatan for the community. This study aims to make the basic concepts of implementing good governance in the City of Padang in terms of BPJS Health Services known and well understood by the community and the government apparatus of the City of Padang. This study seeks to uncover the problems that arise and are faced by the Padang City BPJS Office related to the concepts of good governance by describing a number of facts found through observation and interview methods at the BPJS Kesehatan Branch Office in Padan City. The data analysis techniques used in this study include data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the concepts of good governance in BPJS Health Services in the city of Padang can be said to be running well, but it still requires improvement in order to obtain a better assessment.